The "Wizard of Oz" as a Monetary Allegory - Rockoff, Hugh (Journal of Political Economy, 1990)
The Wonderful Wizard of Oz, perhaps America's favorite children's story, is also an informed comment on the battle over free silver in the 1890s. The characters in the story represent real figures such as William Jennings Bryan. This paper interprets the allegory for economists and economic historians, illuminating a number of elements left unexplained by critics concerned with the politics of the allegory. It also reexamines Bryan and the case for free silver. Far from being monetary cranks, the advocates of free silver had a strong argument on both theoretical and empirical grounds.